DYNAMIC MECHANICAL PROPERTIES AND CONSTITUTIVE MODEL MODIFICATION OF SUS304 STAINLESS STEEL USED IN CARBODIES OF TRAINS - LIU YuXin; ZHU Tao; XIAO ShouNe; YANG GuangWu; YANG Bing; WANG MingMeng (Jixie qiangdu, 2022)
In order to study the dynamic mechanical properties of SUS304 stainless steel commonly used in rail vehicles, tensile tests under wide strain rates of 0.000 2 s-1～500 s-1 were carried out respectively. The test results show that SUS304 stainless steel exhibits strain hardening during dynamic stretching. As the strain rate increases, the material exhibits a strain rate strengthening effect. At the same time, a certain thermal softening effect is produced. To accurately describe the dynamic mechanical properties of the material, the Johnson-Cook model of the material at room temperature was first established. On this basis, adiabatic temperature rise is introduced, and a modified Johnson-Cook model considering plastic strain and strain rate correlation is established. The modified Johnson-Cook model can better describe the dynamic mechanical characteristics of SUS304 stainless steel, which is the characteristic that the stress gradually weakens with the increase of strain and strain rate. This modified model provides a basic basis for the crashworthiness analysis of the rail vehicle body structure.